2018
DOI: 10.3390/ijms19071843
|View full text |Cite
|
Sign up to set email alerts
|

Post-Receptor Inhibitors of the GHR-JAK2-STAT Pathway in the Growth Hormone Signal Transduction

Abstract: The growth hormone (GH) plays a key role in the regulation of metabolic processes in an organism. Determination of the correct structure and functioning of the growth hormone receptor (GHR) allowed for a more detailed research of its post-receptor regulators, which substantially influences its signal transduction. This review is focused on the description of the post-receptor inhibitors of the GHR-JAK2-STAT pathway, which is one of the most important pathways in the transduction of the somatotropic axis signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 134 publications
(164 reference statements)
1
25
0
Order By: Relevance
“… targeted knockin mutations to the box 1 sequence of GHR in mice, which inhibited JAK2 activation by GH in vivo , and found that the activation of hepatic ERK via Src did not decrease. Src family kinase is reported to associate constitutively with GHR, and acts in parallel to JAK2/STAT5, which activates RAS and then ERK1/2 . The GHR/JAK2/STAT pathway has the most pronounced role in the somatotropic axis signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… targeted knockin mutations to the box 1 sequence of GHR in mice, which inhibited JAK2 activation by GH in vivo , and found that the activation of hepatic ERK via Src did not decrease. Src family kinase is reported to associate constitutively with GHR, and acts in parallel to JAK2/STAT5, which activates RAS and then ERK1/2 . The GHR/JAK2/STAT pathway has the most pronounced role in the somatotropic axis signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone, a peptide hormone produced in the anterior pituitary gland, induces cell division, regeneration and growth . It first binds to preformed growth hormone (GH) receptor (GHR) dimers and then causes a conformational change, further activating the GHR, JAK2 (Janus Kinase 2) and STAT5 signaling pathway and inducing the synthesis of insulin‐like growth factor I (IGF‐I) in liver . The effect of the GH/IGF‐1 system on cancer progression recently has been the focus of much interest.…”
mentioning
confidence: 99%
“…Both GH and IGF1 are involved in somatotropic axis (GH-GHR-IGF1). IGF1 is a very potent growth factor that stimulates growth in all cell types playing a critical role in pre-and postnatal growth [34]. Therefore, further exploration of changes in GH and IGF1 proteins caused by GHR-AS-EST might provide insights into the biological significance of GHR-AS-EST and details on its regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For signaling, GH needs to bind to a GHR dimer, which modifies the position of the GHR extracellular domains and activates JAK2-STAT signaling [17,34]. GHBP inhibits the binding of GH to GHR by forming a GH-GHBP complex [20].…”
Section: Ghr-as-est Blocks Signal Transmission From Gh To Ghr and Fromentioning
confidence: 99%
“…As is logical, so that vascular homeostasis is fulfilled correctly, negative regulation mechanisms must exist to prevent an excess of intracellular signaling by GH after its interaction with its membrane receptor. The negative regulation of GH signaling is mainly performed by intracellular protein tyrosine phosphatases 1B and H1, suppressors of cytokine signaling (SOCS, 1, 2 and 3), sirtuin 1, protein inhibitors of activated STAT (1, 3 and 4), cytokine-inducible SH2-containing protein (CIS), and Src homology 2 (SH2) domain containing protein tyrosine phosphatase (SHP) [82] (Figure 1). Given the different systems that act on the negative regulation of GH signaling pathways, there must be a perfect balance between them to prevent a pathological situation from occurring.…”
Section: Figurementioning
confidence: 99%